Challenging endeavor to integrate gallium and carbon via direct bonding to evolve GaN on diamond architecture. (1st January 2018) - Kim, Jong Cheol; Lee, Jinhyung; Kim, Jongsik; Singh, Rajiv K.; Jawali, Puneet; Subhash, Ghatu; Lee, Haigun; Arjunan, Arul Chakkaravarthi
Abstract: This paper depicts efforts for fabricating GaN on diamond microstructure through direct bonding between Ga and C, while excluding the use of adhesive interlayer during spark plasma sintering (SPS) process. The resulting GaN on diamond architecture is seemingly successful, as suggested by macroscopic morphological observations. The microscopic inspection using high-resolution transmission electron microscopy (HRTEM), however, shows a unique, off-the-chart interlayer configuration, wherein the components are migrated, etched, or fused to tentatively form multiple crystal phases. These phases can be constructed based on their utmost stabilities among all possible phases thermodynamically driven under or near the SPS conditions. Graphical abstract: